1989
DOI: 10.1002/ijc.2910430211
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapy with recombinant interferons gamma and alpha in patients with unfavorable prognosis of chronic myelocytic leukemia: Clinical responsiveness to recombinant ifn‐α correlates with the degree of receptor down‐regulation

Abstract: Natural and recombinant interferons (IFNs) have already demonstrated therapeutic efficacy, including cytogenetic remissions, in patients with chronic myelocytic leukemia (CML). We investigated at the level of ligand-receptor interaction the question whether heterogeneity of receptor number or affinity might contribute to primary or secondary treatment failures in CML. We therefore analyzed IFN-gamma and IFN-alpha receptor expression and regulation during treatment with recombinant IFN-gamma and IFN-alpha in 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Pretreatment with LPS (0.1 #g/ml) also blocked MAP kinase activation induced by both stimuli but was only effective in C3H/HeN macrophages ( Table 1). Downregulation of kinase activation has been attributed to depletion of receptors by ligand binding (25,26). However, if LPS and LPP shared a receptor, then pretreatment with LPS should have contributed to the reduction of MAP kinase activation in C3H/HeJ macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with LPS (0.1 #g/ml) also blocked MAP kinase activation induced by both stimuli but was only effective in C3H/HeN macrophages ( Table 1). Downregulation of kinase activation has been attributed to depletion of receptors by ligand binding (25,26). However, if LPS and LPP shared a receptor, then pretreatment with LPS should have contributed to the reduction of MAP kinase activation in C3H/HeJ macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…So far, this type of regulation has been described for a number of receptors for growth factors and cytokines. For example, IFN-u receptors, which have been extensively studied, were found to be downregulated after treatment with IFN-a in all the cell types tested both in vitro and in vivo [19] .This down-regulation is considered as a marker of the action of IFN-a and correlates with the clinical responses of patients with B cell malignancies such as hairy cell leukemia and non-Hodgkin's lymphoma [16,20,211 and also with chronic myeloid leukemia [22] , i. e. tumors which are particularly sensitive to IFN-a therapy [23]. By contrast, down-regulation of insulin receptors seems to correlate with insulin resistance in some forms of type I1 diabetes [24].…”
Section: Discussionmentioning
confidence: 99%
“…In good responders, a permanent ‘down‐regulated’ state of IFNAR2 was maintained at least for 12 months after the initiation of the IFN α therapy, indicating that long‐term down‐regulation of IFN receptor seems to reflect a continuous response to IFN α . Earlier studies, which were performed by receptor‐binding assays because IFN receptor subunits had not been identified yet, reported the modulations of type I IFN receptor on PBMNCs during IFN α therapy in CML patients (31–33), where the decrease of ligand‐receptor binding occurred in patients achieving a good response but not in patients with a poor response to IFN α . One of these studies also reported that the down‐regulation of the IFN receptor occurred even with in vitro treatment of IFN α , and that this decreased binding was due to a loss in number of IFN receptors, not due to decrease of affinity to the ligand (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated whether IFN receptor expression and its down‐regulation are related to the clinical response to IFN α in hematological malignancies such as hairy cell leukemia (29), low‐grade malignant lymphoma (30), and CML. Comprehensive studies on IFN receptor expressions in relation to the clinical response to IFN α therapy in CML have been rather limited, except in earlier studies by receptor‐binding assays (31–33). Even after molecular cloning of the IFNAR1 and IFNAR2, studies regarding the IFN receptor expression in clinical samples of hematological malignancies have been very limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation